Diskontinuitaet und Tradition im System der tschechischen Anredepronomina (1700-1850) - Betsch, Michael (Slavistische Beitraege, 2000)
As a prerequisite for further interpretations, the present study will first cover the data of the investigated development in a comprehensive source analysis. These linguistic historical data can then be related to the background of external linguistic history and general typological assumptions about the development of styling systems. In addition, the peculiarities of Czech development should be made clear by comparison with the corresponding developments in Polish and German. On this basis, an overall characteristic of the development of the pronominal salutation in Czech and an assessment of the role of National Rebirth will be attempted.